Enhanced Optical Bistability of a Metasurface Based on Asymmetrically Optimized Mirror-Induced Magnetic Anapole States - Rui Xu; Sen Tian; Yujia Wen; Guoxiong Cai (Applied Sciences)
In the field of modern optical computing and communication, optical bistability plays a crucial role. With a weak third-order nonlinear coefficient, low switch thresholds of optical bistability from Si-based nanophotonic structures remain a challenge. In this work, a metasurface consisting of silicon nanostrip arrays placed on the optically thick silver film is proposed. The light–matter interaction is enhanced by mirror-inducing the magnetic anapole states (MASs) and asymmetrically optimizing its silicon nanostrip. Numerical results show that the average enhancement factor (EF) of an electric field can be greatly enhanced to be 1524.8. Moreover, the optical bistability of the proposed metasurface achieves the thresholds of ION-OFF and IOFF-ON of 8.5 MW/cm2 and 7.1 MW/cm2, respectively, which is the lowest threshold when compared to the previous works based on silicon nanostructures. The angular dependance of the bistability performance is also investigated. This work facilitates the proposed hybrid metasurface in the fields of miniaturized all-optical switches and modulators, which are key components in optical computing and communication.